Functioning of the Integrated System of Care for Stroke Patients Treated with Mechanical Thrombectomy Based on the Case Report - Adriana Borodzicz; Ewelina Bąk; Iwona Drabczak; Sylwia Krzemińska (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Mechanical thrombectomy is a treatment method used in the event of ischemic stroke, caused by obstruction of a large artery. This method is used to treat stroke in its acute phase. An integrated health care system is about placing the patient in need of help at the centre of the procedure. In such a system, the patient receives support and treatment methods in various fields and from various specialists.